Undergraduate nursing students’ attitude towards online classes during lockdown period in India: imposed or interested? - Gaur, Rakhi; Mudgal, Shiv Kumar; Kaur, Simarjeet; Sharma, Ravikant (International Journal Of Community Medicine And Public Health, 2020)
Background: Online classes were never been a part of regular habit in India. But due to corona pandemic every institute is offering online classes whether medical or nursing institutes. Aim was to ascertain the attitude towards online classes among undergraduate nursing students during lockdown period. Methods: This cross-sectional descriptive survey was conducted on 394 undergraduate nursing students in which samples were chosen through convenient sampling technique. A valid and reliable self-structured questionnaire based on 5 point Likert scale was used to ascertain the attitude of undergraduate nursing students towards online classes and data were analysed using descriptive and inferential statistics in SPSS version 23. Results: More than two-third (76%) participants showed unfavorable attitude towards online classes. There was a significant difference between age, residence, father and mother education with participants’ year of study (p<0.05). Overall mean score for attitude towards online classes was 73.37 (SD±23.52) and there was no significant difference between overall attitude score with participants’ year of study. Only one subscale (interest to computer and intention to adopt component) had significant difference (p=0.011) among participants. There was significant association found among gender, mother education and family income with their year of study (p<0.05). Conclusions: Online classes may have lots of advantages over traditional classes yet it does not seem to be of much interest among undergraduate nursing students in India and they are not willing to consider it on a regular basis. Policy makers should find the way to make online classes more interesting.